Benign Ovarian Cysts with Raised CA-125 Levels: Do We Need to Evaluate the Fallopian Tubes? - Sharma, Devesh; Vinocha, Anjali (Journal of Laboratory Physicians, 2020)
Objectives It is not clearly known whether some benign (simple) ovarian cysts can convert into cancerous cysts. Size of cyst and wall abnormalities do predict the potentiality of malignancy. Not many studies have been done to explore the malignant potential of large-sized (> 5 cm) unilocular ovarian cysts without wall abnormalities. This study evaluated the correlation between ultrasonographic size of benign ovarian cysts and carbohydrate antigen 125 (CA-125) levels.Methodology Sixty (60) premenopausal women were recruited for the study preoperatively, based on transvaginal ultrasound (TVUS) findings present in the case record sheet received along with the CA-125 sample in the biochemistry laboratories. Those cases with elevated CA-125 levels were selected, where patients had unilocular ovarian cysts without wall abnormalities. CA-125 was done using ECLIA methodology (Cobas e411, Germany). Statistical correlation was calculated between the ovarian cyst size and CA-125 levels using Spearman’s Rho coefficient.Results Mean age group of subjects were 29.7 ± 7.3 years and mean value of CA-125 (normal < 35 IU/mL) was found to be increased: 118.0 ± 147.1 IU/mL so was the mean diameter of cysts (cut off ≤ 5 cm): 48.6 ± 59.8 cm. No correlation was found between CA-125 levels and volume of ovarian cyst (r = 0.005, p = 0.680) for all subjects.Conclusions The lack of correlation between size of ovarian cysts and CA-125 levels provides a hint that the ovarian cyst epithelium does not directly express CA-125 and it may come from sites like the fallopian tube. Thus, raised level of CA-125 in benign ovarian cyst should be followed-up more closely, demanding assessment of fallopian tubes for early diagnosis of ovarian cancer. Also, algorithms can be explored to include size of ovarian cyst and CA 125 levels to predict ovarian cancer.
Keywords: ovarian cyst; CA 125 antigen; ovarian neoplasm